2014
DOI: 10.1063/1.4868729
|View full text |Cite
|
Sign up to set email alerts
|

Standing electromagnetic solitons in hot ultra-relativistic electron-positron plasmas

Abstract: Using a one-dimensional self-consistent fluid model, we investigate standing relativistic bright solitons in hot electron-positron plasmas. The positron dynamics is taken into account. A set of nonlinear coupled differential equations describing the evolution of electromagnetic waves in fully relativistic two-fluid plasma is derived analytically and solved numerically. As a necessary condition for the existence of standing solitons the system should be relativistic. For the case of ultra-relativistic plasma, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Lontano et al [28] have shown that relativistic electromagnetic solitons in a warm quasi-neutral electron-ion plasma have a large amplitude in the case of higher electron and ion temperatures. [32][33][34][35][36], and e-p pairs/plasmas have been generated in the laboratory as well [37][38][39][40][41]. This is done for all the three types of the perturbing pulses ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Lontano et al [28] have shown that relativistic electromagnetic solitons in a warm quasi-neutral electron-ion plasma have a large amplitude in the case of higher electron and ion temperatures. [32][33][34][35][36], and e-p pairs/plasmas have been generated in the laboratory as well [37][38][39][40][41]. This is done for all the three types of the perturbing pulses ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The quantity represents the species of the plasma. Now, in the case where the thermal pressure is much smaller than the magnetic one, the kinetic dispersion relation of the system with regard for relativistic corrections can be written as ( − k ) (ln + ln ) (15) represents the effects of the temperature and the inhomogeneity of the plasma, and and ⊥ are the components of the wave number which are oriented in parallel and perpendicularly to the magnetic field, respectively. Note that, in the limit → 0, Eq.…”
Section: Relativistic Kinetic Dispersion Relation Of Cherenkov Radiationmentioning
confidence: 99%
“…The main nonlinear effects in the propagation of intense electromagnetic pulses through a plasma arise from the relativistic variation of the electron mass (relativistic nonlinearity) and from a perturbation in c ○ E. HEIDARI, 2017 the electron density, which takes place because of the ponderomotive forces due to the radiation fields (strict nonlinearity). Both these effects change the effective dielectric constant of the plasma medium for the propagation of electromagnetic waves and lead to a coupling between the transverse electromagnetic wave and the longitudinal waves in the plasma medium [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that as the flow velocity of the plasma changes, the shape of the solitary wave shows two opposing behaviors depending on whether the solitary wave velocity is larger than the flow velocity or smaller than the flow velocity. Relativistic solitary waves in pure electron-positron plasma have been researched by many authors [13][14][15][16][17][18][19][20][21]. Lontano et al [14] derived the soliton-like distributions of electromagnetic radiation based on a relativistic kinetic model.…”
Section: Introductionmentioning
confidence: 99%